2018
DOI: 10.1371/journal.pone.0196636
|View full text |Cite
|
Sign up to set email alerts
|

Dance training is superior to repetitive physical exercise in inducing brain plasticity in the elderly

Abstract: Animal research indicates that a combination of physical activity and sensory enrichment has the largest and the only sustaining effect on adult neuroplasticity. Dancing has been suggested as a human homologue to this combined intervention as it poses demands on both physical and cognitive functions. For the present exploratory study, we designed an especially challenging dance program in which our elderly participants constantly had to learn novel and increasingly difficult choreographies. This six-month-long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
1
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(174 citation statements)
references
References 67 publications
4
147
1
10
Order By: Relevance
“…Some evidence shows that cognitive stimulating environments lead to brain volumetric advantages and better cognitive performances. These effects are common to physiological [24][25][26] and initial pathological ageing, [27][28][29] suggesting that neuroplasticity is maintained even in diseased brains, regardless of the specific clinical picture or the underlying pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence shows that cognitive stimulating environments lead to brain volumetric advantages and better cognitive performances. These effects are common to physiological [24][25][26] and initial pathological ageing, [27][28][29] suggesting that neuroplasticity is maintained even in diseased brains, regardless of the specific clinical picture or the underlying pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…Although an increase in hippocampal volume was reported after both aerobic [24] and resistance training in older adults [130], few brain imaging studies are currently available that directly compare different types of physical training. For instance, it was observed that dancing conducted for several months led to a greater increase in cortical grey matter in frontal and temporal regions [298][299][300] and in hippocampal volumes [301] than a combination of resistance, endurance, and flexibility training. Hence, comparing different types of physical interventions (e.g., resistance training vs. aerobic training vs. dancing) with regard to their effectiveness in evoking structural and functional brain changes is an interesting topic for further studies.…”
Section: Structural Brain Changes and Cognition In Response To Resistmentioning
confidence: 99%
“…This might be related to the cognitive stimulation more or less explicitly embedded in the game scenario of exergames. But also coordinative exercises such as dancing as well as aerobic and strength exercises have been shown to improve cognitive functions (12,(105)(106)(107)(108)(109)(110)(111). In the Active@Home exergame, several components were included with rather high cognitive demands (step-based cognitive training, dancing, Tai Chi-inspired strength exercises).…”
Section: <001mentioning
confidence: 99%